HUBUNGAN ANTARA TOKOH MASYARAKAT DENGAN MORAL REMAJA DI DESA BANJARREJO, BATANGHARI, LAMPUNG TIMUR TAHUN 2010 - Sudirin, Sudirin, (JURNAL TAPIS, 2011)
The Islamic religious leaders in the village have obligation against adolescents morality. Even though this role has been done by the islamic religious leaders, but some adolescents in Banjarrejo village have bad morality. This research aims to explore relationship of development of islamic religious leaders to adolescents morality in Banjarrejo village, Batanghari, East Lampung. The research is quantitative  research in which the data obtained by interview and documentation. The result shows that there is some influences of Islamic religious leaders in rural adolescent moral development  Banjarrejo  East Lampung  in 2010Keywords: Peran, Tokoh Masyarakat, Akhlak Remaja